Geometrie und Topologie von Trajektorienoptimierung für vollautomatisches Fahren - Ruf, Miriam (Karlsruher Schriften zur Anthropomatik / Lehrstuhl für Interaktive Echtzeitsysteme, Karlsruher Institut für Technologie ; Fraunhofer-Inst. für Optronik, Systemtechnik und Bildauswertung IOSB Karlsruhe, 2018)
In order to establish general principles in the topic of motion planning for fully-automated driving, an intuitive problem statement in the form of an Euler-Lagrange Model is derived and transformed into a corresponding Hidden Markov Model for global optimization. Geometric and topologic considerations lead to a probabilistic environment modelling in combination with the C² model and result in general conclusions about the structure of traffic situations.